Advances in Wireless Sensor Networks 6th China Conference, CWSN 2012, Huangshan, China, October 25-27, 2012, Revised Selected Papers - Wang, Ruchuan; Xiao, Fu.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 6th China Conference on Advances in Wireless Sensor Networks, held in Huangshan, China, in October 2012. The 70 revised full papers were carefully reviewed and selected from 458 submissions. The papers cover a wide range of topics including in the wireless sensor network fields nodes systems, infrastructures, communication protocols, and data management.
Design and Implementation of Cooperative Platform for Multiple Devices Based on Multi-Agent System in Ubiquitous Networking Environment -- Research on Data Fault Tolerance Mechanism Based on ECT in Cloud Storage.- Live Migration of Virtual Machines Based on DPDT.- Storage and Management Strategy for Heterogeneous Data Stream Based on Mutation Information.- A Data Gathering Approach for Wireless Sensor Network with Quadrotor-Based Mobile Sink Node.- A Node Design for Intelligent Traffic Monitoring Based on Magnetic Sensor.- A Lightweight RFID Mutual Authentication Protocol with Ownership Transfer.- Network Topology Effects on Reachback Firefly Algorithm in Slot Synchronization.- Opportunistic Routing in Multi-Power Wireless Sensor Networks.- Improved DV-Hop Localization Algorithm Based on RSSI Value and Hop Correction.- A Candidate Forwarder Set Based Channel Assignment for Opportunistic Routing in Multi-radio Wireless Mesh Networks.- The Analysis of Anchor Placement for Self-localization Algorithm in Wireless Sensor Networks.- Low-Cost VR System Based on Wireless Accelerometer Sensor.- Using Sensor Web to Sharing Data of Ocean Observing Systems.- A Survey on Event Processing for CPS.- MND: An Information of Detected Neighbors Based Multi-channel Neighbor Discovery Protocol for Wireless Sensor Networks.- Research on Network Malicious Code Dendritic Cell Immune Algorithm Based on Fuzzy Weighted Support Vector Machine.- Ant Colony Based Routing Strategy in UAV Delay Tolerant Networks.- Deploying Three-Dimensional Mobile Sensor Networks Based on Virtual Forces Algorithm -- A Module Harvesting Wind and Solar Energy for Wireless Sensor Node -- Integrated Tracking Initiation Mechanism Based on Probability for Bearing-Only Sensor Networks.- Graph-Based Multi-hop Cooperative MIMO Scheme for Heterogeneous WSN -- Research of Adaptive Frequency Hopping Technology in WIA-PA Industrial Wireless Network -- Novel Three-Party Password-Based Authenticated Key Exchange Protocol for Wireless Sensor Networks -- TFA: A Scale-Free Network Approach to Topology Formation in Underwater Acoustic Sensor Networks -- Full-View Coverage Algorithm in Camera Sensor Networks with Random Deployment -- A Novel Real-Time Traffic Information Collection System Based on Smartphone -- Detection Performance Optimization Based Power Allocation between Sensing and Communication in Wireless Sensor Networks -- A User-Oriented Resource Management Model for the Internet of Things -- Distributed Joint Optimal Control of Power and Rate with Clustered Routing Protocol in Wireless Sensor Networks -- Sweep Coverage with Mobile Sensors on Two-Way Road -- H-Mac: A Hybrid MAC Protocol for VANET.- Placement and Selection Algorithm of Reference Nodes in WSN Localization.- A Distributed Broadcast Protocol of Wireless Sensor Networks Based on Dynamic Multi-channel MAC Protocol -- Mobile Agent Based Coding Aware Multipath Routing for Wireless Sensor Network -- Maximizing the Lifetime of Unreliable Sensor Networks with Delay Constraint via Genetic Algorithm.- Wireless Sensor Network Time Synchronization Algorithm Based on SFD -- Dynamic Bluetooth Packet Selection Strategy Based on Wi-Fi White-Space Prediction -- An Energy-Aware Routing for Maximum Lifetime in Wireless Sensor Networks -- Research and Implementation of the System Manager Based on Android Platform for Wireless Sensor Network -- The Key Technologies and Development Research of Chinese Light Industry IOT Application -- The Research of Routing Forwarding Strategies in DTNs Based on Convergence Point -- Analysis and Construction of Efficient RFID Authentication Protocol with Backward Privacy -- A New TCP Design for Satellite-HAP Networks -- Layered Pre-selection Model Based on the Trust Mechanism for Web Educational Resources -- Cyber-Physical Traffic Systems: Architecture and Implementation Techniques -- An Energy Efficiency Evaluation Model Based on the Mechanical Work System -- An Energy Efficiency Dynamic Routing Protocol for Farmland Moisture Sensor Networks -- A Novel Method for Passive Objective Adaption Localization Using Sensing Link -- Frequency Selection in ECRT-Based Radio Interferometric Ranging -- Design and Implementation of Testing Platform for Middleware of Wireless Sensor Networks -- A Partitioned Link Scheduling Algorithm for Wireless Multimedia Sensor Networks -- Research of Green Moisture Monitoring Node Based on Hardware Modular Design -- Energy-Efficient Multi-hop Routing Algorithm Based on LEACH -- A Regularity-Based Connectivity Analysis of Three-Dimensional Wireless Sensor Networks -- On the Optimum Placement and Number Selection of Relay Nodes in Multi-hop Routing for Minimizing Communication Power Consumption -- AR-HS: Ant Routing Optimized Algorithm on HAPs-Satellite Integrated Networks -- R-AODV: A Cognitive AODV Routing Algorithm in Wireless Network -- An Overview on Node Behavior Trust Evaluation in Ad Hoc Network -- Array-Forming Wireless Sensor Network Framework for Target Monitoring and System Scheduling -- A Reliable Congestion Avoidance Protocol for Wireless Sensor Networks -- A Cooperative Routing Algorithm for Maximizing Network Lifetime -- A Dynamic Web Services Selection Algorithm Based on Trust Model for Grid Environment -- A Real-Time Micro-sensor Motion Capture System -- Periodic Data Prediction Algorithm in Wireless Sensor Networks -- Filtering Algorithms for Chirp-Spread-Spectrum Ranging -- A Secure DV-Hop Localization Algorithm Based on Secure Beacon Nodes -- Improvement on Localization Error and Adaptability in DV-Hop Algorithm -- The Chained Mesh-Under Routing (C-MUR) for Improving IPv6 Packet Arrival Rate over Wireless Sensor Networks -- Compressed Sensing Data Fusion of Monitoring Cyanobacteria Bloom-Forming. Research on Data Fault Tolerance Mechanism Based on ECT in Cloud Storage.- Live Migration of Virtual Machines Based on DPDT.- Storage and Management Strategy for Heterogeneous Data Stream Based on Mutation Information.- A Data Gathering Approach for Wireless Sensor Network with Quadrotor-Based Mobile Sink Node.- A Node Design for Intelligent Traffic Monitoring Based on Magnetic Sensor.- A Lightweight RFID Mutual Authentication Protocol with Ownership Transfer.- Network Topology Effects on Reachback Firefly Algorithm in Slot Synchronization.- Opportunistic Routing in Multi-Power Wireless Sensor Networks.- Improved DV-Hop Localization Algorithm Based on RSSI Value and Hop Correction.- A Candidate Forwarder Set Based Channel Assignment for Opportunistic Routing in Multi-radio Wireless Mesh Networks.- The Analysis of Anchor Placement for Self-localization Algorithm in Wireless Sensor Networks.- Low-Cost VR System Based on Wireless Accelerometer Sensor.- Using Sensor Web to Sharing Data of Ocean Observing Systems.- A Survey on Event Processing for CPS.- MND: An Information of Detected Neighbors Based Multi-channel Neighbor Discovery Protocol for Wireless Sensor Networks.- Research on Network Malicious Code Dendritic Cell Immune Algorithm Based on Fuzzy Weighted Support Vector Machine.- Ant Colony Based Routing Strategy in UAV Delay Tolerant Networks.- Deploying Three-Dimensional Mobile Sensor Networks Based on Virtual Forces Algorithm -- A Module Harvesting Wind and Solar Energy for Wireless Sensor Node -- Integrated Tracking Initiation Mechanism Based on Probability for Bearing-Only Sensor Networks.- Graph-Based Multi-hop Cooperative MIMO Scheme for Heterogeneous WSN -- Research of Adaptive Frequency Hopping Technology in WIA-PA Industrial Wireless Network -- Novel Three-Party Password-Based Authenticated Key Exchange Protocol for Wireless Sensor Networks -- TFA: A Scale-Free Network Approach to Topology Formation in Underwater Acoustic Sensor Networks -- Full-View Coverage Algorithm in Camera Sensor Networks with Random Deployment -- A Novel Real-Time Traffic Information Collection System Based on Smartphone -- Detection Performance Optimization Based Power Allocation between Sensing and Communication in Wireless Sensor Networks -- A User-Oriented Resource Management Model for the Internet of Things -- Distributed Joint Optimal Control of Power and Rate with Clustered Routing Protocol in Wireless Sensor Networks -- Sweep Coverage with Mobile Sensors on Two-Way Road -- H-Mac: A Hybrid MAC Protocol for VANET.- Placement and Selection Algorithm of Reference Nodes in WSN Localization.- A Distributed Broadcast Protocol of Wireless Sensor Networks Based on Dynamic Multi-channel MAC Protocol -- Mobile Agent Based Coding Aware Multipath Routing for Wireless Sensor Network -- Maximizing the Lifetime of Unreliable Sensor Networks with Delay Constraint via Genetic Algorithm.- Wireless Sensor Network Time Synchronization Algorithm Based on SFD -- Dynamic Bluetooth Packet Selection Strategy Based on Wi-Fi White-Space Prediction -- An Energy-Aware Routing for Maximum Lifetime in Wireless Sensor Networks -- Research and Implementation of the System Manager Based on Android Platform for Wireless Sensor Network -- The Key Technologies and Development Research of Chinese Light Industry IOT Application -- The Research of Routing Forwarding Strategies in DTNs Based on Convergence Point -- Analysis and Construction of Efficient RFID Authentication Protocol with Backward Privacy -- A New TCP Design for Satellite-HAP Networks -- Layered Pre-selection Model Based on the Trust Mechanism for Web Educational Resources -- Cyber-Physical Traffic Systems: Architecture and Implementation Techniques -- An Energy Efficiency Evaluation Model Based on the Mechanical Work System -- An Energy Efficiency Dynamic Routing Protocol for Farmland Moisture Sensor Networks -- A Novel Method for Passive Objective Adaption Localization Using Sensing Link -- Frequency Selection in ECRT-Based Radio Interferometric Ranging -- Design and Implementation of Testing Platform for Middleware of Wireless Sensor Networks -- A Partitioned Link Scheduling Algorithm .
Keywords: Computer communication systems; Architecture, Computer; Algorithms; Computer Communication Networks; Computer System Implementation; Algorithm Analysis and Problem Complexity